الكفايات التدريسية اللازمة للمعلمين بالمدارس الحكومية الفلسطينية في ضوء متطلبات الثورة الصناعة الرابعة - ضياء عزمي فالح صالح
Teachers in Palestinian public schools face significant difficulty in interacting with digital technology, in terms of using and employing it during class, due to the absence of teaching competencies that qualify them to possess technical, professional, and technological skills and methods in the educational process. This study answers a main question: What are the teaching competencies required for teachers of the upper basic stage in Palestinian public schools in light of the requirements of the Fourth Industrial Revolution? This study also aims to explore the teaching competencies required for teachers of the upper basic stage in Palestinian public schools in light of the requirements of the Fourth Industrial Revolution. The analytical descriptive approach was used, and the questionnaire and interview were the data collection instruments. A random sample of 360 male and female teachers was selected from a population that represents all male and female teachers at public basic schools in the northern Palestinian governorates with a total of 4,737 male and female teachers. To answer the research questions, the normal distribution test, percentages and frequencies, arithmetic mean and relative arithmetic mean, variance and standard deviation, multivariate Cronbach's alpha test (MANOVA) were used to obtain the research results. The data were analyzed using statistical treatment with the Statistical Package for the Social Sciences (SPSS) program. The study obtained several results, most importantly that the response score of the research sample regarding the requirements of the Fourth Industrial Revolution for teachers of the upper basic stage in Palestinian public schools amounted to 79.49%. The response score of the research sample regarding the teaching competencies required for teachers of the upper basic stage in Palestinian public schools in light of the requirements of the Fourth Industrial Revolution were 77.3%, 82.2%, and 83.8% for the cognitive, professional, and emotional domains, respectively. There were no differences in the degree of scores of teachers of the upper basic stage in Palestinian public schools for the necessary teaching competencies in light of the requirements of the Fourth Industrial Revolution by the variables of gender, number of years of experience, educational qualification, and directorate.